Aplikasi Pos Pelayanan Hukum pada Kantor Kejaksaan Negeri Watansoppeng - Firdayani Firdayani; Zul Rachmat; Rahmawati Rahmawati (STMIK Amika Soppeng, 2025)
Developments at this time are increasingly rapidly making life changes in the needs of information technology and the world of work. So it takes speed in working with technology that can make work faster and more efficient. At this time, legal services or the provision of legal services by the State Attorney (JPN) in writing or orally to the public, which includes individuals and legal entities and at the legal service post are still carried out by means of the community coming to the state prosecutor's office to conduct consultations so that This requires time to perform services, so the purpose of this research is to create a Web-Based Legal Service Post Application at the Soppeng District Attorney's Office. By using the waterfall research method where in making the application there is analysis, design, implementation, testing and maintenance so that this research can produce a Web-Based Legal Service Post Application that can facilitate the public and prosecutors' employees in the legal service process so that this activity can be carried out without having to visit straight to the office.